2015
DOI: 10.1109/te.2015.2405895
|View full text |Cite
|
Sign up to set email alerts
|

Virtualization for Cost-Effective Teaching of Assembly Language Programming

Abstract: Abstract-A virtual system that emulates an ARM-based processor machine has been created to replace a traditional hardware-based system for teaching assembly language. The proposed virtual system integrates, in a single environment, all the development tools necessary to deliver introductory or advanced courses on modern assembly language programming. The virtual system runs a Linux operating system in either a graphical or console mode on a Windows or Linux host machine. No software licenses or extra hardware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…That RISC microcontroller (RMCU) is very popular among the students, teachers, amateurs, engineers, scientists and hobbyists for building electronics projects [9,10,11]. There are 133 one clock cycle instructions implemented.…”
Section: Microprocessor Atmega128mentioning
confidence: 99%
“…That RISC microcontroller (RMCU) is very popular among the students, teachers, amateurs, engineers, scientists and hobbyists for building electronics projects [9,10,11]. There are 133 one clock cycle instructions implemented.…”
Section: Microprocessor Atmega128mentioning
confidence: 99%
“…Also, PBL could support self-directed learning but it requires suitable tools to guide the students through the process. In [10], the authors explained the use of an emulator as a virtual tool for learning ARM based processor. In their literature, they showed that the students are more interested and they felt very easy in learning the concepts using this tool.…”
Section: Introductionmentioning
confidence: 99%
“…[8]- [10] focuses entirely on a hands-on training/laboratory experiences and does not provide inputs on integration of both theory and lab sessions. [11] highlights the delivery of content for Digital Systems course, along with laboratory component.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of digital education relates to supporting the learner to acquire software development competencies. The main lines of research in this field include cost-effective simulation of programming environments [8,20], dynamic adaptation of e-training [9,36], human-machine interaction [31,34] and collaborative learning [21,22]. Recently, the research attention has been also devoted to developing specific digital teaching paradigms [5].…”
Section: Introductionmentioning
confidence: 99%